2022
DOI: 10.1177/14789299221082037
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Inequality and Political Participation: The Moderating Role of Ideology

Abstract: While much research has been devoted to the effects of inequality on political participation, little attention has been paid to how different kinds of subjective perceptions of social inequality affect citizens’ political behaviour. This is important since these perceptions shape the message that reaches political decision-makers when addressing concerns over social inequalities. This article differentiates between sociotropic and egocentric perceptions of social inequality and explores to what extent individu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 65 publications
(135 reference statements)
1
3
0
1
Order By: Relevance
“…While PEIS is positively associated with behavior in the middle and upper classes, the wage gap is negatively associated with the same behavior in the upper class. Tracing results from previous studies (e.g., García-Castro et al, 2022;Silagadze et al, 2022), these findings suggest how the dimensions of perceived inequality considered play a differential role on political action. In our case, wealthier individuals who perceive a larger gap between the wages of two occupations may not be spurred to take political action, possibly because of their economically priviledged situation.…”
Section: Discussionsupporting
confidence: 59%
“…While PEIS is positively associated with behavior in the middle and upper classes, the wage gap is negatively associated with the same behavior in the upper class. Tracing results from previous studies (e.g., García-Castro et al, 2022;Silagadze et al, 2022), these findings suggest how the dimensions of perceived inequality considered play a differential role on political action. In our case, wealthier individuals who perceive a larger gap between the wages of two occupations may not be spurred to take political action, possibly because of their economically priviledged situation.…”
Section: Discussionsupporting
confidence: 59%
“…How did failure to secure primary-market tickets cause differences in Swifties' political attitudes and behaviors? Research has shown that both the emotion of anger and sociotropic perceptions of unfairness can affect political attitudes and mobilize political participation (e.g., Mutz and Mondak 1997;Valentino et al 2011;Silagadze et al 2023). We preregistered these feelings as two possible causal mechanisms underlying our hypothesized effects to test empirically.…”
Section: A9 Assessing Causal Mechanismsmentioning
confidence: 99%
“…Following this line of reasoning, we assume that people evaluate political decisions either based on their perceived consequences for society at large, or their consequences for the individual in question. A recent study shows that sociotropic and egocentric perceptions of social inequalities have different associations with political participation since people with higher levels of sociotropic concerns about inequalities are more likely to take action (Silagadze et al, 2022). Other studies suggest that self-interest plays a larger role when the policy stakes for the individual are great, clear, and salient (Chong et al, 2001;Haselswerdt, 2020).…”
Section: Participatory Inequalities and Implications For Legitimacymentioning
confidence: 99%
“…Furthermore, the effects may differ depending on the type of legitimacy at stake (Scharpf, 1999;Schmidt, 2013). Finally, the impact of inequalities might be contingent on the nature of the decisions (Silagadze et al, 2022) and the type of participatory process (el-Wakil and Strebel, 2022). It is crucial to examine the interplay between these factors to appreciate how participatory inequalities affect legitimacy.…”
Section: Introductionmentioning
confidence: 99%